2006
DOI: 10.1530/eje.1.02138
|View full text |Cite
|
Sign up to set email alerts
|

Increased T-helper interferon-γ-secreting cells in obese children

Abstract: Objective: Leptin, an adipocyte-secreted hormone, has emerged as a potential candidate for the link between obesity and the proinflammatory state. Specifically, leptin modulates T-helper (Th) cells toward a Th1 phenotype, with the secretion of proinflammatory cytokines. The aim of this study was to evaluate the Th1/Th2 balance in obese children and its relation with hormonal and metabolic features. Study design: In 50 obese children and 20 control children, we measured the CD4-positive Th cells that secrete in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(135 citation statements)
references
References 38 publications
(29 reference statements)
13
115
0
2
Order By: Relevance
“…In general, both CD4 T-and B-cell counts and percentages are higher in obese individuals than in lean individuals, and these increases are associated with risk factors of metabolic diseases, e.g., higher triglyceride and lower high-density lipoprotein (HDL) cholesterol levels. It has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15).…”
Section: Introductionsupporting
confidence: 50%
“…In general, both CD4 T-and B-cell counts and percentages are higher in obese individuals than in lean individuals, and these increases are associated with risk factors of metabolic diseases, e.g., higher triglyceride and lower high-density lipoprotein (HDL) cholesterol levels. It has also been reported that peripheral T cells in obese individuals are somewhat activated, displaying increased expression levels of surface CD25 (a subunit of the IL2 receptor) and polarization towards a pro-inflammatory type-1 (T H 1) phenotype (10)(11)(12). It should be noted here that metabolic abnormalities, including serum levels of high triglyceride, low HDL cholesterol and fatty liver development, have been reported in association with radiation dose among A-bomb survivors (13)(14)(15).…”
Section: Introductionsupporting
confidence: 50%
“…This seems to be in contrast with the findings showing that the systemic immune response in obese children is skewed to Th1 profile, as demonstrated by an increase in numbers of IFN-gsecreting helper T cells. 10 In addition to the possibility that the increase in Th1 response in obesity might be age-and/or gender-related, it should be noted that it can also occur through downregulation of Th1 counter-regulatory Th2 response characterized by IL-4 secretion, 12 which was not assessed in our study.…”
Section: Discussionmentioning
confidence: 87%
“…8 Moreover, some recent findings suggest that inflammation-related tissue damage in organ-specific autoimmunity could be associated with the IL-23/IL-17-dependent T-helper cell response (that is, Th17 response), rather than with the activity of IL-12/IFN-g cytokine axis as the main driving power behind the so-called Th1 response. 9 Although there are some data indicating that Th1 response might be reduced in malnourished and increased in obese children, [10][11][12] IL-23…”
Section: Introductionmentioning
confidence: 99%
“…(31) found no significant difference between baseline concentrations of IFN-γ in obese versus nonobese women; whereas, Pacifico and cols. (32) showed that obesity is associated with increased T-helper IFN-γ secreting cells in obese children. This inconsistency might be explained by age and sex related response of immune cells or it can also occur because of counterregulatory mechanisms of Th1 versus Th2 immune cell response as revealed by Sumarac-Dumanovic and cols.…”
Section: Discussionmentioning
confidence: 99%